Full-Term Human Placental Macrophages Eliminate Coxiella burnetii Through an IFN-γ Autocrine Loop - Mezouar, Soraya; Benammar, Imene; Boumaza, Asma; Diallo, Aïssatou Bailo; Chartier, Céline; Buffat, Christophe; Boudjarane, John; Halfon, Philippe; Katsogiannou, Maria; Mege, Jean-Louis (Frontiers in Microbiology, 2019)
The intracellular bacterium Coxiella burnetii is responsible for Q fever, an infectious disease that increases the risk of abortion, preterm labor and stillbirth in pregnant women. At the placental level, it has been shown that C. burnetii replicates in BeWo trophoblast cell line and inhibits the activation and maturation of decidual dendritic cells. Although tissue macrophages are known to be targeted by C. burnetii, no studies have investigated the interplay between placental macrophages and C. burnetii. Here, CD14+ macrophages from forty-six full-term placentas were isolated by positive selection. They consisted of a mixed population of maternal and fetal origin as shown by genotype analysis. We showed that C. burnetii organisms infected placental macrophages after 4 hours. When these infected macrophages were incubated for an additional 9-day culture, they completely eliminated organisms as shown by quantitative PCR. The ability of placental macrophages to form multinucleated giant cells was not affected by C. burnetii infection. The transcriptional immune response of placental macrophages to C. burnetii was investigated using quantitative real-time RT-PCR on 8 inflammatory and 10 immunoregulatory genes. C. burnetii clearly induced an inflammatory profile. Interestingly, the production by placental macrophages of interferon-γ, a cytokine known to be involved in efficient immune responses, was dramatically increased in response to C. burnetii. In addition, a clear correlation between interferon-production and C. burnetii elimination was found, suggesting that macrophages from full-term placentas eliminate C. burnetii under the control of an autocrine production of interferon-.